Manufacture and Sensor’s Characterization for Optimizing the Manufacture of Resistance Sensors Based on Honeycomb and Honey Market - Arum, Ayu Sakila; Cholidina, Dyah Imas; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
This research aims to identify resistance sensors based on honeycomb and honey market. It was conducted in three stages, namely sensor design, sensor manufacturing and sensor characterization. The sensor scheme has been made by software fritzing. The tools used in the sensor manufacture are PCB sensors, resistors and copper wire. The tools used in sensor characterization are provided by power supply, CRO and samples. Sensor testing is done by varied the sample into 6 variations accurately 5ml, 10ml, 15ml, 20ml, 25ml, and 30ml. Data generated from the sensor in the form of voltage. Repetition on each volume variation was 10 times. Then, It was be processed by calculating the compatibility and the average of the voltage produced along with its uncertainty. The results showed the average of the voltage generated with the uncertainty at 5ml volume (9,052 ± 0,001) V and (8,682 ± 0.017) V, for volume of 10ml (9,040 ± 0.025) V and (8,531 ± 0.050) V, for volume of 15ml (8,947 ± 0.073) V and (8.230 ± 0.018) V, for volume of 20ml (8.999 ± 0.073) V and (8,209 ± 0.007) V, for volume of 25ml (8.967 ± 0.080) V and (7.689 ± 0.048)V and for volume of 30ml (8,925 ± 0,040) V and (8,284 ± 0,018) V. Repeatibility has produced on this sensor was obtained from two samples, honeycomb by 90.919% and honey market by 94.432%. Based on the results obtained from the calculation, it can be determined that the transfer function was V = 9.06853x-0.0045828571 and V = 8.72453x-0.0259257143. The linear correlation coefficient obtained by 95.9%. This research will be used for optimizing the manufacture of resistance sensors with good characteristics.